Palliative care for people with Alzheimer's disease - Mahon, Margaret M. (Nursing philosophy, 2008)
The task of aligning the philosophical and clinical perspectives on ethics is a challenging one. Clinical practice informs philosophy, not merely by supplying cases, but through shaping and testing philosophical concepts in the reality of the clinical world. In this paper we explore several aspects of the relationship between the philosophical and the clinical within a framework of palliative care for people living with Alzheimer's disease. We suggest that health professionals have a moral obligation to question previous assumptions concerning the quality of life among people with Alzheimer's, and to address the question: does the concept of palliative care properly embrace people with severe dementia? We propose an ethic of palliative care for people with Alzheimer's that is based, not on the traditionally understood principle of autonomy, but on the need to listen to those living with the disease, acknowledging their profound loss of cognitive abilities, with a focus on preventing and relieving suffering, and improving the individual's quality of life.